CO2 and CH4 adsorption on different rank coals: A thermodynamics study of surface potential, Gibbs free energy change and entropy loss. (1st January 2021) - Du, Xidong; Cheng, Yugang; Liu, Zhenjian; Yin, Hong; Wu, Tengfei; Huo, Liang; Shu, Couxian
Highlights: The preferential adsorption of CO2 over CH4 improves with coal rank. Pore structure of coal affects the thermodynamics of adsorption of CO2 and CH4 . Adsorbed CO2 has a more ordered configuration than CH4 on different rank coals. Abstract: In this paper, the pore structures of three different rank coals sampled from China (anthracite, bituminous coal and lignite) were characterized by CO2 and N2 adsorption. The isothermal adsorption curves of CO2 and CH4 on three samples were measured by gravimetric method and fitted by Langmuir model. The preferential selectivity ( α CO2/CH4 ) was calculated using the Langmuir parameters of CO2 and CH4, and the Henry's coefficient ( K H ) was obtained with the help of virial equation. More importantly, a comparative analysis of adsorption thermodynamics of CO2 and CH4 on three different rank coals, including surface potential ( Ω ), Gibbs free energy change (Δ G ) and entropy loss (Δ S ), was presented according to the adsorption data. It is found that the uptakes of CO2 and CH4 on anthracite are the largest, followed by lignite and bituminous coal in sequence. α CO2/CH4 increases with the increase of coal rank. Low temperature helps injected CO2 to displace pre-adsorbed CH4 . The K H values on anthracite are the biggest, while K H values on bituminous coal are the smallest. Ω, Δ G and Δ S of CO2 and CH4 all exhibit a U-shaped function with maturity. Anthracite has the highest Ω, Δ G and Δ S, while bituminous coal has the lowest Ω, Δ G and Δ S . The thermodynamics parameters of Ω, Δ G and Δ S are affected by pore size distributions of three coals. Ω, Δ G and Δ S of CH4 are smaller than those of CO2 . CO2 adsorption on coal is more favorable and spontaneous, and adsorbed CO2 molecules form a more efficient packing on coal.